Visualization Analysis of Research on Inefficient Stock Space by Mapping Knowledge Domains - Wangyang Gui; Xu Li; Bin Xu (Buildings)
Inefficient stock space use in urban and rural areas causes economic losses and environmental harm, needing better solutions. Currently, this field is constrained by a relatively underdeveloped research history, which has led to the lack of a comprehensive theoretical framework and established solution methodologies. Therefore, it is crucial to clarify the principles of spatial evolution within theoretical approaches to promote the rapid advancement and practical application of subsequent theories. This effort will improve the understanding of the effective utilization of inefficient inventory space and encourage critical analysis by systematically reviewing the developmental trajectory of previous research. This study aims to conduct a thorough analysis of the developmental trajectory, evaluation frameworks, and strategies for the effective utilization of inefficient space by utilizing the Web of Science (WOS) and China National Knowledge Infrastructure (CNKI) databases. Through the application of CiteSpace for visualization and analysis, the research investigates the pertinent literature on inefficient stock space, covering the period from 2004 to the present. The results show that research on inefficient stock space exhibits diverse characteristics, with WOS publications focusing on four primary dimensions, namely land space reuse, the establishment of evaluation systems, environmental governance, and urban and rural development planning. Conversely, CNKI publications tend to prioritize spatial optimization design and the mechanisms of planning and development. In relation to policy frameworks and evolutionary trends, the study of inefficient stock space in urban and rural contexts has evolved through three distinct phases, the embryonic stage (2004–2013), the exploration stage (2013–2020), and the growth stage (2020–present). While the effective utilization of currently inefficient stock space in urban areas has been addressed through various initiatives, there remains a significant gap in research focused on rural areas, highlighting the necessity for an enhanced exploration of urban–rural coupling mechanisms. Additionally, the efficient utilization of inefficient stock space in both urban and rural environments is a multidisciplinary challenge that requires the development of innovative urban and rural development models aligned with the principles of sustainable development, drawing insights from disciplines such as economics, architecture, and urban planning.